PENGARUH BUDAYA KERJA DAN KOMPENSASI TERHADAP KINERJA TENAGA MEDIS PADABADAN LAYANAN UMUM DAERAH (BLUD) RUMAH SAKIT MAYJEN HM. RYACUDU KABUPATEN LAMPUNG UTARA - . Herlintati (e-JKPP, 2017)
One of the aspects that play a role in improving the performance of medical personnel Public Service Agency (BLUD) Hospital Major General HM. Ryacudu North Lampung Regency is the work culture and good compensation. Problems identified in this study are; application of work culture is not entirely good, the compensation has not been good and the performance of medical personnel has not been good.               The aim of research to identify and analyze the extent of the influence of work culture and compensation to the performance of medical personnel Public Service Agency (BLUD) Major General HM Hospital. Ryacudu North Lampung regency. The method used in this study is a survey and case studies with quantitative analysis methods.               Results of research Simultaneously there is significant influence between work culture and compensation to the performance of Public Service Agency (BLUD) Major General HM Hospital. Ryacudu North Lampung regency. The result of the calculation result of simultaneous hypothesis testing between work culture and compensation to the performance of Public Service Agency (BLUD) Major General HM Hospital. Ryacudu North Lampung regency showed that P (Sig) = 0,000 <α = 0.05. Multiple linear regression calculation results between culture and compensation work together on the performance of Public Service Agency (BLUD) Major General HM Hospital. Ryacudu North Lampung regency obtained Y = 12.108 + 1,617X1 + 1,129X2. Keywork: Work Culture, Compensation, Performance Medical.